Pengaruh Efektivitas Sistem Informasi Akuntansi Pada Kinerja Karyawan Bank Perkreditan Rakyat (Bpr) Di Kabupaten Gianyar Dengan Budaya Organisasi Dan Motivasi Kerja Sebagai Pemoderasi - Ni Kd Sioaji Yamawati; I Gusti Ayu Ratih Permata Dewi (Universitas Mahendradatta Denpasar, 2021)
This study aims to influence the Effectiveness of Accounting Information Systems on Employee Performance with Organizational Culture and Work Motivation as Moderation. Employee performance can be affected by the existence of an accounting information system. This research was conducted at BPR in Gianyar Regency using a questionnaire and distributed to employees related to the Accounting Information System. The data analysis technique used is the Partial Least Square (PLS) approach. The results showed that the effectiveness of the Accounting Information System had an effect on employee performance. Furthermore, organizational culture and work motivation are able to moderate the Effect of the Effectiveness of Accounting Information Systems on Employee Performance